APPARATUS FOR ADDRESSED VIBROMECHANICAL STIMULATION OF INTELLECTUAL ABILITY - D. I. Sagaidak; S. V. Shilko; V. V. Yaschuk (Приборы и методы измерений, 2015)
The method of addressed vibromechanical stimulation, apparatus for its realization and implementation example has been described. The development is seemed available and effective mean of intellectual ability improvement in responsible and social important kinds of activity.